The Last Supper of Chicano Heroes : Selected Works of José Antonio Burciaga - Burciaga, Jose Antonio (Book collections on Project MUSE., 2008)
"Widely considered one of the most important voices in the Chicano literary canon, Burciaga was a pioneer who exposed inequities and cultural difficulties through humor, art, and deceptively simple prose. In this anthology and tribute, Mimi Gladstein and Daniel Chacon bring together dozens of remarkable examples of Burciaga's work. His work never demonstrates machismo or sexism, as he believed strongly that all Chicano voices are equally valuable. Best known for his books Weedee Peepo, Drink Cultura, and Undocumented Love/ Amor Indocumentado, Burciaga was also a poet, cartoonist, founding member of the comedy troupe Cultura Clash, and a talented muralist whose well-known work The Last Supper of Chicano Heroes became almost more famous than the man." "This first and only collection of Burciaga's work features thirty-eight illustrations and incorporates previously unpublished essays and drawings, including selections from his manuscript "The Temple Gang," a memoir he was writing at the time of his death. In addition, Gladstein and Chacon address Burciaga's importance to Chicano letters. This rich compendium is an important contribution not only to Chicano literature but also to the preservation of the creative, spiritual, and political voice of a talented and passionate man."--Jacket.